(untitled) (Baghdad Science Journal, 2024)
This study was conducted for the purpose of measuring the quality of water in the wells of the Fayda District by measuring the water quality index, On the basis of chemical and physical standards that were measured using modern devices, techniques and classical methods. 168 samples were collected and analyzed based on several parameters involving, Water temperature, pH, Electrical Conductivity(EC), Total dissolved solid, Turbidity, Alkalinity, NO3-2, Cl−, Ca+2 Mg+2 SO4-2, Dissolved Oxygen(DO) and Total hardness(TH). The data showed variation of the investigated parameters in samples as follows: 18.417 to 22.567 °C and 7.65 to 8.39 for water pH, 5.685 to 8.283mg/L for DO, 1.200 to 3.225 NTU for Turbidity, 456.25 to 2300.00 μS/cm for EC, 259.33 to 1471 mg/L and 204.08 to 1363 mg/L for TDS and TH , 204.42 to 435.75 mg/L and 122.67 to 622.08 mg/L for TA and Calcium, 85.33 to 747 mg/L and 12.842 to 100.100 mg/L for Magnesium and Chloride, 20.450 to 200.833 mg/L and 2.200 to 7.350 mg/L for Sulfate and Nitrate. the water quality index (WQI) in the districts of Bakr 167.33–183.32 , Krebany 115.4–124.069, Fayda 108.44–113.07 , Domes1 104.96–119.87, Domes2 109.66–119.90, Kranke 101.58–111.35 and Jambor 99.89–110.24 District are higher than the allowable limits according to the World Health Organization standards (WHO) for drinking water. The (WQI) for the 168 samples ranged from 78.15 to 183.32. Krebany, Fayda, Domes 1, Domes 2, Kranke and Jambor wells all exceeded the value of 100. About 61.3% of water samples were of poor quality for drinking purposes